Pharmacodynamic Thresholds for Beta-Lactam Antibiotics: A Story of Mouse Versus Man - Berry, Angela V.; Kuti, Joseph L. (Frontiers in Pharmacology, 2022)
Beta-lactams remain a critical member of our antibiotic armamentarium and are among the most commonly prescribed antibiotic classes in the inpatient setting. For these agents, the percentage of time that the free concentration remains above the minimum inhibitory concentration (%fT>MIC) of the pathogen has been shown to be the best predictor of antibacterial killing effects. However, debate remains about the quantity of fT>MIC exposure needed for successful clinical response. While pre-clinical animal based studies, such as the neutropenic thigh infection model, have been widely used to support dosing regimen selection for clinical development and susceptibility breakpoint evaluation, pharmacodynamic based studies in human patients are used validate exposures needed in the clinic and for guidance during therapeutic drug monitoring (TDM). For the majority of studied beta-lactams, pre-clinical animal studies routinely demonstrated the fT>MIC should exceed approximately 40-70% fT>MIC to achieve 1 log reductions in colony forming units. In contrast, clinical studies tend to suggest higher exposures may be needed, but tremendous variability exists study to study. Herein, we will review and critique pre-clinical versus human-based pharmacodynamic studies aimed at determining beta-lactam exposure thresholds, so as to determine which targets may be best suited for optimal dosage selection, TDM, and for susceptibility breakpoint determination. Based on our review of murine and clinical literature on beta-lactam pharmacodynamic thresholds, murine based targets specific to each antibiotic are most useful during dosage regimen development and susceptibility breakpoint assessment, while a range of exposures between 50-100% fT>MIC are reasonable to define the beta-lactam TDM therapeutic window for most infections.